Access and permanence of women with disabilities in higher education: Reflecting from the perspective of inclusion (Research, Society and Development, 2021)
Brazil is a country marked by countless inequalities, as well as episodes and narratives of discrimination against multiple minorities, among them are women.  In the context of this historical and cultural construction, the female subjects result in discriminatory and objectification procedures.  And when these women bring with them some disability they live a double abjection, having their stories marked by invisibility and social segregation.  By deciding to break the vicious circle of denial and to occupy the various spaces, such as joining universities, they face different barriers.  In this sense, we seek to analyze the access to higher education and the conclusion of studies, which are timely for women with disabilities, in order to understand whether these spaces have been a mechanism for guaranteeing the autonomy and independence of these women.  We conducted this study at two universities located in different regions of the country, in the Northwest Fluminense Institute of higher Education (INFES/UFF), located in the city of Santo Antonio de Padua/RJ and in the Federal University of Pernambuco/Agreste Academic Center (UFPE/CAA), located in the city of Caruaru/PE. Among the results obtained, we evidenced that, despite a legal framework, retaining the access and permanence of people with disabilities to higher education, there are still many necessary advances, in order to guarantee the inclusion, in fact, of these people to these spaces.  And when we talk about women with disabilities, these paradigms of inclusion maximize even more, because under them are the various socio-historical constructions that inhibit their effective participation in society and the realization of their rights.